Models of role interaction in oral academic discourse - Tolstonogova, Irina V. (Journal of the Belarusian State University. Philology, 2018)
The article is devoted to the study of the process of interaction in oral academic discourse, its components and determinants, to the identification and description of communicative roles of a teacher and students, to the systematization of their speech behaviour patterns and to the construction of corresponding models. Each model of role interaction is analyzed from the point of view of its structure, intentions of communicants, means of linguistic and speech representation, frequency of use and speech product volume of communicants. The material of the study is scripts of practical classes in English.